Европейские модели организации и управления природопользования - Андерсон, Н.В. (Економічні інновації, 2015)
У статті розглядаються моделі організації та управління природокористування в країнах ЄС для можливого впровадження європейського досвіду в Україні. Виділено специфічні особливості державного управління низки європейських країн для адаптації національного природоохоронного законодавства України до міжнародних вимог і стандартів ЄС. The article deals with the models of organization and management of natural resources in the EU for the possible introduction of the European experience in Ukraine. Highlighted the specific features of public administration in several European countries to adapt national environmental legislation of Ukraine to the international requirements and standards of the EU.